Prenatal Diagnosis and Molecular Cytogenetic Characterization of a Small Supernumerary Marker Chromosome Derived From Chromosome 8 - Chih-Ping Chen; Ming Chen; Tsang-Ming Ko; Gwo-Chin Ma; Fuu-Jen Tsai; Ming-Song Tsai; Pei-Chen Wu; Chen-Chi Lee; Li-Feng Chen; Wayseen Wang (Elsevier, 2010)
Objective: To present prenatal diagnosis and molecular cytogenetic characterization of a small supernumerary marker chromosome (sSMC) derived from chromosome 8 by multiplex ligation-dependent probe amplification (MLPA), fluorescence in situ hybridization (FISH), spectral karyotyping (SKY) and array comparative genomic hybridization (aCGH). Case Report: A 42-year-old woman, gravida 6, para 3, underwent amniocentesis at 19 gestational weeks because of advanced maternal age. Amniocentesis revealed a de novo ring-shaped sSMC in all 13 colonies of the amniocytes. The karyotype was 47,XY,+mar. The MLPA showed duplications of 8p11.21-specific probes. At 24 gestational weeks, level II ultrasound revealed a left multicystic kidney in the fetus. Other internal organs were unremarkable. Repeat amniocentesis revealed a karyotype of 47,XY,+mar[25]/46,XY[2]. The sSMC was characterized by SKY and FISH, which showed a chromosome 8 origin of the sSMC. Oligonucleotide-based aCGH demonstrated a 4.4-Mb duplication of 8p11.21q11.1 [arr cgh 8p11.21q11.1 (42,637,263-47,062,180)×3]. The karyotype was 47,XY,+r(8) (p11.21q11.1)[25]/46,XY[2]. Polymorphic DNA marker analysis revealed no uniparental disomy for chromosome 8. The woman elected to continue the pregnancy and at 34 gestational weeks, a 1,820 g male baby without craniofacial dysmorphism was delivered. At the age of 1 month, the infant was apparently normal except for left multicystic kidney disease and mild ventriculomegaly. Conclusion: MLPA, SKY and aCGH are helpful in genetic counseling of prenatally detected sSMCs by providing the immediate information on the origin and the genetic contents of the sSMC.